Mathematical modelling to predict mechanical properties of Copper (C101) feedstock in continuous extrusion - Kumar Sinha D.; Kumar S.; Kumar A.; Yadav A. (My University, 2025)
The continuous extrusion process is a process for producing endless profiles with a high degree of accuracy. The two important and vital process parameters are extrusion wheel velocity and product diameter which affect the mechanical and metallurgical properties of the material. In this work, continuous extrusion of pure copper (C101) rod has been carried out on commercial setup TBJ 350 for feedstock diameter of 9.5 mm at different extrusion wheel velocities and product diameters using different die sizes. The yield strength and percent elongation of extruded feedstock at different wheel velocities and product diameters has been estimated by carrying out the tensile test. The continuous extrusion process has been carried out based on two factor three-level central composite rotatable design using response surface methodology. A mathematical model has been developed to predict the mechanical properties of the extruded feedstock through continuous extrusion process and its validation has been carried out using ANOVA technique. © Published under licence by IOP Publishing Ltd.